Analytical validation of a novel bioassay for thyroid-stimulating immunoglobulin - Olivo, Paul D.; Kim, Hannah; Miao, Lynn; Houtz, Jeffery A.; Kahaly, George J. (Frontiers in Endocrinology, 2025)
BackgroundA novel and rapid cell-based bioassay, Turbo TSI, for measurement of thyroid-stimulating immunoglobulins (TSI) was recently reported. An assessment of the analytical performance of this TSI bioassay is described herein.MethodsThawed cells from Turbo TSI kits were treated with different concentrations of a World Health Organization (WHO) international standard (IS) TSI-positive serum. TSI was measured as a function of luciferase activity measured as relative light units (RLU) and converted into international units per liter (IU/L). Analytical performance studies were performed on numerous samples, over multiple days, by two users at two sites.ResultsThe limit of blank, limit of detection and limit of quantitation were determined to be 0.007 IU/L, 0.014 IU/L, and 0.021 IU/L, respectively. Receiver operator characteristics (ROC) analysis determined the cut-off to be 0.0241 IU/L with an area under the curve of 0.984. The linear range was shown to be from 0.015 to 11.958 IU/L. The intra-laboratory precision was ≤15%CV. The overall reproducibility of the assay was ≤20%CV for five concentrations (0.06 to 5.16 IU/L). Interference and cross reactivity studies with a variety of substances showed that the assay was robust. The Turbo TSI bioassay demonstrated 95.2% (95% CI 83.3-98.1) positive percent agreement and 94.8% (95% CI 90.9-97.1) negative percent agreement with an FDA-cleared bioassay (Thyretain® TSI) using serum from 295 patients with autoimmune thyroid disease.ConclusionsThe Turbo TSI bioassay exhibits excellent analytical performance and a high level of reproducibility. The performance compared well with Thyretain® TSI, an FDA-cleared TSI bioassay.